Comparative Analysis of Virology and Pathogenesis of SARS-CoV-2 and HIV Infections: Implications for Public Health and Treatment Strategies - Olebo DF; Igwe MC (Infection and Drug Resistance)
David Francis Olebo,1– 3 Matthew Chibunna Igwe1 1Department of Public Health, School of Allied Health Sciences, Kampala International University, Western Campus, Uganda; 2Komase Ebenezer Research Centre, Fort Portal City, Uganda; 3Makerere University Walter Reed Program, Kampala City, UgandaCorrespondence: David Francis Olebo; Matthew Chibunna Igwe, Email olebodavidfrancis@gmail.com; igwechibunna@gmail.comIntroduction: Coronavirus Disease 19 (COVID-19), caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), and Human Immunodeficiency Virus (HIV) are significant 21st-century pandemics with distinct virological and clinical characteristics. COVID-19 primarily presents as an acute respiratory illness, while HIV leads to chronic immune suppression. Understanding their differences can enhance public health strategies and treatment approaches.Purpose: This narrative review compares the virology, transmission, immune responses, and clinical outcomes of SARS-CoV-2 and HIV to inform treatment strategies and public health interventions.Methods: A narrative review was conducted, synthesizing data from peer-reviewed literature and expert commentary from 2010 to 2024. Databases such as PubMed, Cochrane Library, and Google Scholar were searched for relevant studies.Results: SARS-CoV-2 primarily spreads through airborne droplets and contaminated surfaces, while HIV transmits through direct contact with infected bodily fluids. The immune response to SARS-CoV-2 involves both innate and adaptive systems, potentially leading to a cytokine storm in severe cases. In contrast, HIV evades the immune system by integrating into host cells, resulting in chronic infection and progressive immune deterioration. Treatment for SARS-CoV-2 focuses on symptom management and prevention, with antiviral medications and vaccines playing crucial roles. Conversely, HIV treatment relies on antiretroviral therapy (ART) to suppress viral replication and maintain immune function.Conclusion: The review highlights the acute nature of SARS-CoV-2 versus the chronic progression of HIV. Tailored prevention and treatment strategies are essential for effective disease management.Recommendations: Public health strategies should address the unique transmission routes and progression of both viruses. Further research into vaccine development and therapeutic interventions is critical for improving disease management.Keywords: COVID-19, HIV, viral transmission, immune response, disease progression